Psychology for the IB Diploma Coursebook - Jacob Solomon (Cambridge, United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2018)
This series supports the latest Psychology syllabus (for first examination in 2019). Delve into human behaviour by studying real cases in this coursebook for the IB Psychology syllabus. Through studies of famous psychologists, students learn about the diversity of human behaviour and the factors that influence our decisions. International case studies and concise definitions of important concepts make this an ideal resource for learners whose first language is not English. Exam-style questions at the end of every chapter help students prepare for assessment. The coursebook covers both Standard and Higher Level content and suggested answers to the coursebook questions are at the back of the book.
Keywords: IBDP - Group-3 - Psychology -- IBDP - Group-3 - Psychology